Production of biodiesel from waste cooking oil using heterogeneous catalyst - Danang Jaya; Tunjung Wahyu Widayati; Hanum Salsabiela; Muhammad Fathan Abdul Majid (Eksergi, 2022)
The world's oil reserves are running low, which makes the government also implement a mandatory B30 policy starting in early 2020. With this policy, it is necessary to develop energy by utilizing renewable energy such as vegetable oil that can be converted into biodiesel. Waste cooking oil is one of the vegetable oils that has the potential to be processed into biodiesel because the use of waste cooking oil in Indonesia is still not developed. In this study, we report the yield of biodiesel from waste cooking oil with variations in the ratio of the number of moles and weight of heterogeneous catalysts. Biodiesel is made by esterification and transesterification with a heterogeneous catalyst (CaO), then a separation process is carried out to separate the biodiesel produced from the by-product in the form of glycerol. The separated biodiesel is then analyzed for density, viscosity, flash point, and pour point. The results showed that the best biodiesel was at a mole ratio of 1:24 with 3% CaO catalyst. Based on the analysis data, this biodiesel has the largest yield of 72.49% with a viscosity value of 4.9806 cSt, a flash point value of 72.5 oC, a pour point value of 0 oC, and a density value of 0.8662 g/ml and calorific value. 8837,302 cal/gram. With the results of the analysis, that are in accordance with the quality standards of SNI 7182:2015.